The association between maternal vitamin D deficiency and postpartum hemorrhage and uterine atony - Anna Sörsjö Stevenazzi; Sofia Pihl; Marie Blomberg; Daniel Axelsson (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Postpartum hemorrhage is the leading cause of maternal morbidity and mortality worldwide. There are several known risk factors for postpartum hemorrhage related to pregnancy and delivery, but less evidence of predisposing factors. Recent research has shown that vitamin D deficiency may increase the risk of cesarean section due to dystocia, based on its effect on striated muscle as well as possible effect on the myometrium. Whether vitamin D deficiency increases the risk for postpartum hemorrhage and especially atonic hemorrhage is unknown. Material and methods This was a retrospective translational study. The study population included 1367 women in Sweden and the main exposure was the serum concentration of 25‐hydroxylated vitamin D at time of delivery. The LIASON® 25 OH vitamin D total assay method was used for analyzing 25‐hydroxylated vitamin D. Vitamin D insufficiency was defined as serum concentration <50 nmol/L and vitamin D deficiency as serum concentrations <25 nmol/L. Primary outcomes were postpartum hemorrhage and severe postpartum hemorrhage defined as bleeding ≥500 mL and ≥ 1000 mL, respectively 2 h after delivery. Secondary outcome was atonic postpartum hemorrhage. Crude and adjusted odds ratios were calculated with 95% confidence intervals using univariable and multivariable logistic regression. Three different adjustment methods were used, adjusting for maternal, obstetrical and neonatal confounders. Results Postpartum hemorrhage and severe postpartum hemorrhage afflicted 31.3% and 6.4% of the women, respectively. Rate of atonic postpartum hemorrhage was 21% in the whole population. Rate of vitamin D insufficiency and deficiency was 57%. Vitamin D insufficiency or deficiency was neither found to be associated with postpartum hemorrhage, nor with atonic postpartum hemorrhage. Conclusions In this study, the vitamin D status of women at the time of delivery was not a predictor of postpartum hemorrhage overall or atonic postpartum hemorrhage.